An assessment of PM10, Co and Tvocs in air-conditioned indoor enviroment - Elly Lawai, Ngalai (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Legislation and assessments on air pollution in Malaysia have focused primarily on ambient air pollution. The issue of indoor air quality has been gaining much public awareness in recent years due to increasing understanding of its effects on employee's health, comfort and productivity. This is of particular concern and deserving more attention, considering that employees spend the majority of their time in indoor environments where they are exposed to high levels of indoor air pollutanty Three major indoor air pollutants, namely particulate matter (PM10), carbon monoxide (CO), and total volatile organic compounds (TVOCs) together with carbon dioxide (C02), humidity, and temperature were measured in ten different locations at UiTM Campus Sarawak. Results of the study show that the levels of particulate matter ranged between 7 Ilg/m3 and 35 Ilg/m3, carbon monoxide between 0.02 ppm and 0.20 ppm, and total volatile organic compounds between 0.15 ppm and 0.38 ppm. These values were low as compared to levels recorded in similar studies conducted by other researchers elsewhere. When comparisons were made against the recommended levels stated in different guidelines and standards issued by various government and environmental agencies, the pollutants levels recorded in this study were within the acceptable ranges. Carbon dioxide levels were relatively high, but still within the acceptable ranges, while humidity exceeded the recommended range at all the locations~'under study. From this study, no specific source of air pollutants was identified, however, building materials, furnishings, office equipments, and occupants' activities could have significantly contributed to the comparatively higher levels of particulate matters and carbon dioxide, and total volatile organic compounds at some of the locations.